Cancer Genome and Tumor Microenvironment - Thomas-Tikhonenko, Andrei (Cancer Genetics, 2010)
Oncogenes and tumor suppressor genes had been traditionally studied in the context of cell proliferation, differentiation, senescence, and survival, four relatively cell-autonomous processes. Consequently, in the late '80s-mid '90s, neoplastic growth was described largely as a net imbalance between cell accumulation and loss, brought about through mutations in cancer genes. In the last ten years, a more holistic understanding of cancer slowly emerged, stressing the importance of interactions between neoplastic and various stromal components: extracellular matrix, basement membranes, fibroblasts, endothelial cells of blood and lymphatic vessels, tumor-infiltrating lymphocytes, etc . Nevertheless, the commonly held view is that changes in tumor microenvironment are "soft-wired", i.e. epigenetic in nature and often reversible. Yet, there exists a large body of evidence suggesting that well-known mutations in cancer genes profoundly affect tumor milieu. In fact, these cell-extrinsic changes might be one of the primary reasons such mutations are preserved in late-stage tumors. Cancer Genome and Tumor Microenvironment reviews how tumor microenvironment and progression can be "hard-wired", i.e. genetically controlled.